Continuous noninvasive arterial pressure: assessment in older and high-risk patients under analgesic sedation - Schramm, Christoph; Baat, Lisa; Plaschke, Konstanze (Blood pressure monitoring, 2011)
Objective - To assess the role of continuous noninvasive arterial pressure (CNAP) in elderly, high-risk patients with pronounced variation in arterial pressure (AP) under analgesic sedation. - Methods - Twenty-nine patients were analyzed while undergoing elective transfemoral aortic valve implantation procedures during periods of normal blood pressure, hypotension, and hypertension with standard invasive arterial pressures (IAP). Systolic, diastolic, and mean IAP were compared with those obtained by CNAP. Data were analyzed to determine precision (i.e. measurement error) and accuracy (i.e. systematic error) during different periods of AP for agreement of the two methods. In addition, we compared the two methods during intervals of functional cardiac arrests (rapid pacing) in terms of amplitude and frequency of rapid changes in AP. - Results - No significant differences in precision were observed between CNAP measurements and IAP measurements. CNAP accuracy was −8.3*, 6.4, and 0.6 mmHg in normotensive, −20.5*, 4.4, and −5.5 mmHg in hypertensive, and −4.8, 9.4, and 4.5 mmHg in hypotensive conditions (*P<0.05). The frequency of AP pairs with a difference of ±15 mmHg (limits of agreement) or less was 59.5, 71.7, and 76.5% in normotensive, 33.1, 72.9, and 66.9% in hypertensive, and 59.5, 71.7, and 76.5% in hypotensive periods for systolic, diastolic, and mean AP, respectively. Rapid pacing intervals showed a significant difference in systolic measurements; whereas the differences between CNAP and IAP for diastolic and mean AP were minimal. - Conclusion - The agreement between the two techniques used in this study of elderly high-risk patients under analgesic sedation is similar to that found in studies performed under general anesthesia. The best agreement was detected in hypotensive periods.